Sistem Penghantaran Nanostructured Lipid Carrier (NLC) Minyak Almond (oleum amygdalae) dan Asam Glikolat sebagai Antioksidan - Rahmadita Sopyanti; Hanifa Rahma; Farendina Suarantika (UNISBA Press, 2024)
Abstract. Nanostructured Lipid Carrier (NLC) is the second generation of lipid nanocarriers developed to increase stability and effectiveness in drug delivery. The general formulation of NLC consists of a combination of solid lipids and liquid lipids. The additional components in the NLC formulation are surfactants which can reduce surface tension. The group of non-ionic surfactants most commonly used for NLC development, for example Poloxamer, Tween, Span, PEG-40 stearate because they have an ionic charge so they do not cause irritation. The use of non-ionic surfactants with a large HLB such as Poloxamer can make the system more hydrophilic and increasing the concentration of non-ionic surfactants can also affect the adsorption of active ingredients. The study was carried out using a Systematic Literature Review (SLR) on articles obtained from reputable databases that met the inclusion and exclusion criteria. The results of the study show that many studies of NLC preparation formulations using poloxamer surfactants produce smaller particle size characteristics. Abstrak. Nanostructured Lipid Carrier (NLC) merupakan generasi kedua dari nanokarier lipid yang dikembangkan untuk meningkatkan kestabilan dan efektivitas dalam penghantaran obat. Formulasi umum NLC terdiri dari kombinasi antara lipid padat dan lipid cair. Adapun komponen tambahan dalam formulasi NLC, yaitu surfaktan yang mampu menurunkan tegangan permukaan. Golongan surfaktan non ionik paling umum digunakan untuk pengembangan NLC contohnya Poloxamer, Tween, Span, PEG-40 stearat sebab memiliki muatan ion sehingga tidak menyebabkan iritasi. Penggunaan surfaktan non ionik dengan HLB besar seperti Poloxamer dapat membuat sistem menjadi lebih hidrofilik dan peningkatan konsentrasi surfaktan non ionik juga dapat mempengaruhi penjerapan bahan aktif. Kajian dilakukan dengan Systematics Literature Review (SLR) terhadap artikel yang diperoleh pada database bereputasi yang memenuhi kriteria inklusi dan eksklusi. Hasil kajian menunjukkan banyak penelitian formulasi sediaan NLC menggunakan surfaktan poloxamer menghasilkan karakteristik ukuran partikel yang lebih kecil.